A cross-sectional study on the correlation between exercise frequency and mental health among university students based on international physical activity questionnaire-short form classification: evidence from undergraduate students aged 18–22 - Du, Xingbin; Jiang, Fugao; Yuan, Shuping (Frontiers in Psychology, 2025)
BackgroundPhysical inactivity is tightly linked to mental health issues. In China, insufficient physical activity is common among university students, and their mental health concerns guarantee critical focus.ObjectiveOur study aims to conduct a cross-sectional investigation to explore the correlation between exercise frequency and mental health among university students, grouped according to the International Physical Activity Questionnaire (IPAQ). It further assesses differences in depressive and anxiety symptoms across groups with different levels of physical activity, to explain the protective influences of exercise on mental health.MethodsA cross-sectional design was adopted, including 430 undergraduate students aged 18–22 from Qufu Normal University and Shandong Huayu University of Technology. Participants were grouped into four groups according to the short form of the IPAQ (IPAQ-SF): frequent exercise group (FEG), occasional exercise group (OEG), infrequent exercise group (IEG), and no exercise group (NEG). Depressive and anxiety symptoms were evaluated utilizing the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 (GAD-7), in turn. Interfering factors including gender, grade level, body mass index (BMI), and sleep quality were managed for. One-way ANOVA and multiple logistic regression analyses were performed.ResultsThe NEG group displayed significantly higher scores for both depression (PHQ-9: 9.12 ± 4.05 vs. 4.62 ± 2.71) and anxiety (GAD-7: 8.54 ± 3.76 vs. 3.85 ± 2.29) compared with the FEG group (p < 0.001). Following adjustment, the risk of depression (OR = 7.85, 95% CI: 3.39–18.17) and anxiety (OR = 6.95, 95% CI: 2.83–17.05) sustained significantly promoted in the NEG group. Sleep quality also differed significantly in the subgroup of groups (p = 0.014), but sensitivity analyses revealed the robustness of the findings.ConclusionThere is a dose–response link between exercise frequency and mental health. Regular physical activity has a significant protective influence against depression and anxiety among university students. Universities are proposed to promote exercise-based intervention strageties to increase students’ mental well-being.